IMPLEMENTASI MANAJEMEN KURIKULUM DAN PEMBELAJARAN MUATAN LOKAL KETERAMPILAN KERJA DI MA SUNAN KALIJAGA DAN MA MIFTAHUL’ ULA KAB. NGANJUK - Sony Eko Dwisaputro (LP2M IAIN Tulungagung, 2017)
This study was motivated by the law No. 20 of 2003 Article 36, 3rd paragraph is one of the grain states that the curriculum prepared in accordance the level of education within the framework Republic of Indonesia covering the working world demands, therefore this study was done in MA Sunan Kalidjaga and MA Miftahul’Ula, because these institutions are the only educational institutions high school / MA in Nganjuk which organizes educational unit level curriculum (SBC) which incorporate skills subjects among others: outomotive, motorcycle industry, fashion and bridal makeup (cosmetology) for MA Sunan Kalijaga, while MA Miftahul’Ula have skills such as: welding and fashion. Job skills program is breaking new ground to provide skills for learners.Keywords: implementation, management of local curriculum, job skills, learning